Effect of level of egg content on the quality of pudding using reconstituted milk: Egg content on pudding quality - Khatun, MA; Islam, MN; Islam, MA (Bangladesh Journal of Animal Science, 2018)
The study was conducted to analyze the physical and chemical parameters of manufactured pudding and to recommend acceptable level of eggs for the manufacture of pudding. Reconstituted milk was prepared by using the instructions given on the packet of whole milk powder. The prepared reconstituted milk was divided into three parts and three different types of puddings were prepared by using 2 eggs, 3 eggs and 4 eggs with reconstituted milk. Amount of milk, sugar and corn flour level was same in all three types. The puddings were designated as A (2 eggs), B (3 eggs) and C (4 eggs) types. Prepared pudding samples were subjected to physical and chemical analysis to monitor their quality. Physical properties (smell, color, consistency and texture) showed pudding that contained 3 eggs obtained the best score (89.13±3.77) from the judges. From chemical analysis, it was observed that 4 eggs containing pudding showed the highest nutritive value as compared to control and other group but organoleptic score was highest for 3 eggs containing pudding. Bang. J. Anim. Sci. 2018. 47 (2):92-97